2003
DOI: 10.1023/a:1023398924124
|View full text |Cite
|
Sign up to set email alerts
|

Dream imagery becomes more intense after 9/11/01.

Abstract: We examined a series of twenty dreams-the last ten dreams recorded before 9111101 and the first ten dreams recorded after 911110 I-from each of sixteen individuals in the United States who regularly record all their dreams. Blind scoring using established scales demonstrated that dreams after 9111/01 were characterized by more intense imagery, but were not longer nor more "dreamlike," compared to data before 9111101. The dreams after 9111101 did not contain significantly more content related to the attacks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
50
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 7 publications
11
50
1
Order By: Relevance
“…After traumatic events dreamers have abundantly emotionally salient experiences that must be worked though and connected with previous memories, which are reflected in elevated dream recall and intensive emotions in dreams (Punamäki, 1999). The intensification of contextualized emotional images in dreams indicates the victims' need to work trough their painful experiences by framing and regulating them (Hartmann & Basile, 2003). No research is available on the impact of trauma on emotional images in children's dreams.…”
mentioning
confidence: 99%
“…After traumatic events dreamers have abundantly emotionally salient experiences that must be worked though and connected with previous memories, which are reflected in elevated dream recall and intensive emotions in dreams (Punamäki, 1999). The intensification of contextualized emotional images in dreams indicates the victims' need to work trough their painful experiences by framing and regulating them (Hartmann & Basile, 2003). No research is available on the impact of trauma on emotional images in children's dreams.…”
mentioning
confidence: 99%
“…To our knowledge, only one previous study used a repeated measures design to examine changes in dream content after the events of September 11. Hartmann and Basile (2003) used the Internet to recruit 16 individuals who provided 324 dream reports primarily from the month before and the month after September 11. They found an increase in the intensity of dream images, as well as trends toward more attack imagery and more fear and terror emotions in dreams after the attacks.…”
mentioning
confidence: 99%
“…Early studies of acute psychological effects in the United States following these events reported evidence of stress/distress, post-traumatic stress symptoms and depression in adults (Ahern et al, 2004;Blanchard et al, 2004;Vlahov et al, 2002) and children (Hoven et al, 2004;Phillips, Prince & Schiebelhut, 2004) although, again, the level of symptomatology could generally be considered to be subclinical. In a preliminary study of the effects on dreaming Hartmann & Basile (2003) recruited 16 people who regularly recorded their dreams, and found a significant increase in the intensity of contextualising imagery in the 10 dreams following September 11 compared to the preceding 10 dreams from each participant.…”
mentioning
confidence: 99%